2004
DOI: 10.1523/jneurosci.5054-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Spinal Cyclooxygenase-2 Participates in the Initiation of Tissue Injury-Induced Hyperalgesia

Abstract: Inhibitors of the isozyme cyclooxygenase-2 (COX-2) represent an important advance in pain management, although where and when these inhibitors can exert their antihyperalgesic actions are not completely understood. Here we show that unlike many peripheral tissues in which COX-2 is only expressed in physiologically significant levels after tissue injury, in the normal rat lumbar spinal cord, the majority of neurons and radial glia constitutively express high levels of COX-2 protein. Immediately after peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 27 publications
3
57
2
2
Order By: Relevance
“…Prolonged barrage of incoming signals from nociceptors causes activation and sensitization of nociceptive neurons (Ji et al, 2003) and activation of glial cells (Samad et al, 2001, Ghilardi et al, 2004 in the spinal dorsal horn. With time, local prostaglandin release from the activated neurons and glia becomes essential for the maintenance of sensitization of adjacent nociceptive neurons [You, 2003 #16157;Watkins, 2001 #8080;Watkins, 2001 #8081].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged barrage of incoming signals from nociceptors causes activation and sensitization of nociceptive neurons (Ji et al, 2003) and activation of glial cells (Samad et al, 2001, Ghilardi et al, 2004 in the spinal dorsal horn. With time, local prostaglandin release from the activated neurons and glia becomes essential for the maintenance of sensitization of adjacent nociceptive neurons [You, 2003 #16157;Watkins, 2001 #8080;Watkins, 2001 #8081].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the formalin test, paw oedema was measured at the base of the right hind paw using a digital micrometer (Mitutoyo Corporation, USA) with an instrumental error of ± (maximum measuring length/75) μm and a resolution of 0.001 mm (Nackley et al, 2003;Ghilardi et al, 2004).…”
Section: Paw Oedemamentioning
confidence: 99%
“…Furthermore, the same authors have already demonstrated that an acute stimulus, such as intraplantar injection of formalin, could lead to an immediate increase in prostaglandin (PG) release (Dirig et al, 1997). It is suggested that this increased PGE 2 release is mediated by COX-2 and not COX-1 pharmacology, and because the effects are observed acutely, this COX-2 must by definition be constitutively expressed (Ghilardi et al, 2004). Indeed, in many peripheral tissues COX-2 is normally expressed at very low levels but is dramatically upregulated after tissue injury (Ghilardi et al, 2004).…”
Section: Local Antinociceptive Effect Of Nsaidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of COX-2 protein in naïve rat spinal cord has been profiled by others, with agreement that it is expressed in dorsal and ventral horn neurons (16) and some debate regarding any presence in radial glia (18), astrocytes (19), or endothelial cells (20). In our experiments, we saw that spinal cords from control and diabetic rats showed COX-2 immunoreactivity only in dorsal horn neurons, motor neurons, and oligodendrocytes, indicating that the increased COX-2 protein and activity observed in diabetes does not involve induction of COX-2 expression in novel cell types.…”
Section: Discussionmentioning
confidence: 75%